2009
DOI: 10.1007/s11104-009-9908-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial endophytes of sweet potato plants

Abstract: Endophytic bacteria associated with sweet potato plants (Ipomoea batatas (L.) Lam.) were isolated, identified and tested for their ability to fix nitrogen, produce indole acetic acid (IAA), and exhibit stress tolerance. Eleven different strains belonging to the genera, Enterobacter, Rahnella, Rhodanobacter, Pseudomonas, Stenotrophomonas, Xanthomonas and Phyllobacterium, were identified. Four strains were shown to produce IAA (a plant growth hormone) and one strain showed the ability to grow in nitrogen free me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 65 publications
(43 reference statements)
4
91
0
3
Order By: Relevance
“…Our results of root length are in accordance with the research findings of Khan et al (2009), who isolated the IAA producing endophyte from sweet potato and showed an excellent root growth when inoculated onto poplar plant (hybrid variety). Similarly, the EBIs isolated from mangrove are known to promote root length of rice seedlings derived from seeds inoculated with EBIs which proves that endophytes are beneficial to non-host plants (Deivanai Subramanian et al, 2014).…”
Section: Results and Discusssionsupporting
confidence: 91%
“…Our results of root length are in accordance with the research findings of Khan et al (2009), who isolated the IAA producing endophyte from sweet potato and showed an excellent root growth when inoculated onto poplar plant (hybrid variety). Similarly, the EBIs isolated from mangrove are known to promote root length of rice seedlings derived from seeds inoculated with EBIs which proves that endophytes are beneficial to non-host plants (Deivanai Subramanian et al, 2014).…”
Section: Results and Discusssionsupporting
confidence: 91%
“…Proteobacteria members were the dominate species in the atmosphere over mountains (Bowers et al, 2012;Vaïtilingom et al, 2012;Temkiv et al, 2012), in the air samples collected on a tower (Fahlgren et al, 2010), and from the troposphere (DeLeon-Rodriguez et al, 2013;Kourtev et al, 2011). In the phylum proteobacteria, the families Phyllobacteriaceae, Methylobacteriaceae, and Xanthomonadaceae were predominately detected from the non-dust samples and are associated with plant bodies or surfaces (Mantelin et al, 2006;Fürnkranz et al, 2008;Khan and Doty, 2009;Fierer and Lennon, 2011). The Betaproteobacteria sequences in the non-dust samples mainly contained the Oxalobacteraceae and Comamonadaceae families, which are commonly dominate in freshwater environments (Nold and Zwart, 1998) and on plant leaves (Redford et al, 2010).…”
Section: Dominant Bacterial Populations In the Air Masses Originated mentioning
confidence: 99%
“…3,4) Acetobacter diazotrophicus, an endophytic nitrogen-xing bacterium, has been isolated from aerial parts of eld-grown sweet potato, sugarcane, and sweet sorghum (Sorghum vulgare), 3,5) and various nitrogen-xing bacteria were shown to colonize the sago palm extensively. 6) In a recent study by Khan and Doty, 7) endophytic bacteria associated with sweet potato plants were isolated, identi ed, and tested for their ability to x nitrogen and exhibit stress tolerance.…”
Section: Introductionmentioning
confidence: 99%